THE RELATIONSHIP BETWEEN ENVIRONMENTAL LAW ENFORCEMENT RELATED TO ENVIRONMENTAL DEGRADATION AND TIN MINING ISSUE IN BANGKA BELITUNG ISLAND - Syafri Hariansah; widya handini (Faculty of Social and Political Sciences University of Bangka Belitung, 2021)
Bangka Belitung faces very serious environmental problems dueto illegal tin mining that give negative impacts to the sustainabilityof ecosystem and human life. Bangka Belitung is the second largestproducer of tin in the world and tin mining in Bangka Belitung hasbeen exploited since long time ago (hundred years). Tin miningactivity basically increase the wealth of the community but itdecreases the environmental stability inshore & offshore. Takinga case study approach, this study was conducted using qualitativemethod by reviewing and analyzing various legal instrument andinformation related to tin mining, the environmental problem, &the community engagement. Besides that, this study addresses thefollowing research questions : What is the background issuesrelating the case between tin mining and environmentaldegradation in Bangka Belitung? How do tin mining activity giveinfluence to this environmental degradation? How far is thecommitment of enforcing the environmental law in this case inline with the commitment of the society? The result concludedthat there’s effort to provide the environmental law fromexploration to post mining reclamation, as well as the thecommunity engagement. But the implementation is not enoughand need more commitment of enforcing the environmental lawthat give the major environmental degradation in Bangka BelitungArea. The implementation of the law itself need to be supervisedby external party and the enforcement need to be increased aswell as the coordination between stakeholders to support theSustainable Development Goals in Indonesia especially in BangkaBelitung.